Factors associated with uptake of human papillomavirus vaccination among adolescent girls in Mettu town, southwest Ethiopia: a school-based cross-sectional study - Asrat Zewdie; Abeza Mitiku Kera; Amin Dawud; Desta Bekele; Desta Hiko (BMJ Open, 2023)
Objective This study was designed to assess the level of uptake of human papillomavirus (HPV) vaccination and its associated factors among school-age adolescent girls.Design School-based cross-sectional study.Setting High schools in Mettu town, southwest Ethiopia, from 5 February to 10 March 2022.Participants Data were collected using a pretested and structured questionnaire through face-to-face interviews with 667 adolescent girls selected via multistage random sampling. Data were entered into EpiData V.3.1 and exported to SPSS V.26 for analysis. Simple binary logistic regression was done, and variables with a p value less than 0.25 were entered into a multivariable logistic regression model; variables with a p value <0.05 were considered significant.Results About half (48.6%) of adolescent girls aged 14–18 years had received the HPV vaccine. Being in the 16–18 years age group (adjusted OR 2.7, 95% CI 1.50 to 4.80), having good knowledge (2.14, 95% CI 1.29 to 3.52), having a positive attitude (5.86, 95% CI 3.51 to 9.76), and getting encouragement from healthcare workers (3.04, 95% CI 1.36 to 6.79), teachers (2.14, 95% CI 1.05 to 4.34) and parents (2.39, 95% CI 1.02 to 5.64) were significantly associated with vaccine uptake.Conclusion The uptake of HPV vaccination was low. Having good knowledge and positive attitude as well as encouragement from parents, healthcare workers and teachers were identified as factors associated with HPV vaccine uptake. Improving knowledge about HPV and involving teachers and parents in the immunisation campaign might help promote HPV vaccine uptake.